2018
DOI: 10.2147/ijn.s150977
|View full text |Cite
|
Sign up to set email alerts
|

Development of biocompatible and VEGF-targeted paclitaxel nanodrugs on albumin and graphene oxide dual-carrier for photothermal-triggered drug delivery in vitro and in vivo

Abstract: In this study, we performed the characterization and synthesis of biocompatible and targeted albumin and graphene oxide (GO) dual-carrier paclitaxel (PTX) nanoparticles for photothermal-triggered tumor therapy. PTX absorbed on GO nanosheets as cores were coated with human serum albumin (HSA), following surface conjugation with monoclonal antibodies (mAb) against vascular endothelial growth factor (VEGF; denoted as mAbVEGF) via polyethylene glycol linker to form targeted nanoparticles (PTX-GHP-VEGF). The spheri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 48 publications
2
25
0
Order By: Relevance
“…Previous studies reported that GO exhibits the ability to allow for the migration and growth of osteoblasts and mesenchymal stem cells and had a greater osteoconductivity ability compared with traditional calcium phosphate ceramics. [47][48][49] Therefore, in this study we fabricated the combined nanofibrous scaffold (GO-PLGA) by the electrospinning technique. GO has received enormous attention in the bone tissue engineering field due to its unique sp 2 carbon domains, large surface area, and hydrophilic functional group structure.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that GO exhibits the ability to allow for the migration and growth of osteoblasts and mesenchymal stem cells and had a greater osteoconductivity ability compared with traditional calcium phosphate ceramics. [47][48][49] Therefore, in this study we fabricated the combined nanofibrous scaffold (GO-PLGA) by the electrospinning technique. GO has received enormous attention in the bone tissue engineering field due to its unique sp 2 carbon domains, large surface area, and hydrophilic functional group structure.…”
Section: Discussionmentioning
confidence: 99%
“…According to literature reports, 36,44 FITC was used to label IR-AFN@PTX and IR-AFN@PTX-FA by physical adsorption. Treat 4T1 cells with FITC-labeled IR-AFN @PTX and IR-AFN@PTX-FA for 5 hrs, then stain with DAPI and lysosomal-specific dye LysoTracker, and observe IR-AFN@PTX and IR-AFN@PTX-FA in cells using commercial LSM.…”
Section: Cellular Uptake Assaymentioning
confidence: 99%
“…34,35 Paclitaxel (PTX) is an FDA-approved chemotherapy with fewer side effects and has a high inhibitory effect on a variety of malignant tumors. 36,37 However, its solubility in water is poor and requires delivery in a solution of Cremophor EL and ethanol for clinical use. 38 Cremophor EL has been reported to have serious side effects such as hypersensitivity reactions and acute renal impairment.…”
Section: Introductionmentioning
confidence: 99%
“…Super‐paramagnetic iron oxide‐reduced graphene oxide nanohybrid has been used as a vehicle for targeted drug delivery and hyperthermia treatment of cancer . VEGF‐targeted paclitaxel nanodrugs on albumin and graphene oxide have been used as a dual‐carrier for photothermal‐triggered drug delivery in vitro and in vivo in human SW‐13 adrenocortical carcinoma cells http://Chitosan. functionalized graphene nanobiocomposite has been fabricated for the codelivery of two anticancer drugs called 3,3′‐diindolylmethane and CPT.…”
Section: Biomedical Applicationsmentioning
confidence: 99%